2023
DOI: 10.3390/foods12071457
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Application of Ultrasound to Homogenize Milk and the Subsequent Pasteurization by Pulsed Electric Field, High Hydrostatic Pressure, and Microwaves

Abstract: The efficacy of applying ultrasound (US) as a system to homogenize emulsions has been widely demonstrated. However, research has not yet shown whether the effect achieved by homogenizing milk with US is modified by subsequent pasteurization treatments that use new processing technologies such as pulsed electric fields (PEF), microwaves (MW), and high hydrostatic pressure (HPP). The aim of this study was, therefore, to optimize the application of US for milk homogenization and to evaluate the effect of PEF, HPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Numerous variables, such as animal genetic merit and breed, lactation stage and parity, time of milking, udder health status, and herd‐level variables like pasture grazing and seasonal calving, are known to affect milk color (Scarso et al, 2017). Astráin‐Redín et al (2023) reported an ∆ E value of 1.4 for milk pasteurized by ultrasound and pulse electrical field. The reduced cubic model can be used to predict ∆ E value at different values of EFI and MFR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous variables, such as animal genetic merit and breed, lactation stage and parity, time of milking, udder health status, and herd‐level variables like pasture grazing and seasonal calving, are known to affect milk color (Scarso et al, 2017). Astráin‐Redín et al (2023) reported an ∆ E value of 1.4 for milk pasteurized by ultrasound and pulse electrical field. The reduced cubic model can be used to predict ∆ E value at different values of EFI and MFR (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…revealed that a* value of FM, CP, and induced electric field reached À1.23, À1.20, and À1.28, respectively. calving, are known to affect milk color(Scarso et al, 2017) Astráin-Redín et al (2023). reported an ΔE value of 1.4 for milk pasteurized by ultrasound and pulse electrical field.…”
mentioning
confidence: 99%
“…In this way, methodologies based on physical properties, which allow the direct or indirect measurement of the applied acoustic energy, are widely used [ 22 ]. These effects have been observed in food matrices subjected to ultrasound-assisted extraction, homogenization, modification, stabilization, and emulsification [ 30 , 31 , 32 , 33 , 34 ].…”
Section: Ultrasound Generation Systemsmentioning
confidence: 99%
“…In this way, methodologies based on physical properties, which allow the direct or indirect measurement of the applied acoustic energy, are widely used [22]. These effects have been observed in food matrices subjected to ultrasound-assisted extraction, homogenization, modification, stabilization, and emulsification [30][31][32][33][34]. The types of acoustic systems (probe or bath) and the processing conditions, such as the frequency, power, duration, temperature, and sample-to-water ratio, influence the performance of ultrasonication.…”
Section: Ultrasound Generation Systemsmentioning
confidence: 99%